Flexible Learning Space of the Child - Jolanta Andrzejewska (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
"Contemporary pre-school education, largely anchored in old codes and paradigms, increasingly does not correspond to current and future challenges. It does not support the potential of every child in the educational process, does not take into account his individual differences" (Andrzejewska 2015, p. 192). Traditional educational solutions, mainly limited to the use of the potential of the kindergarten classroom and the garden by teachers and pre-schoolers, do not emphasise the issues connected with the need to include educational content linked with the socio-cultural contexts of learning processes. These contexts influence the process of representation in the mind and the way of using the knowledge acquired in different conditions. Thus, "the same knowledge learned in different conditions will be differently 'written' in the mind and differently 'used' in new situations" (Klus-Stańska, Kruk 2009, p. 471). The article is an attempt to show the unused potentials of the kindergarten classroom and the need for the teacher to extend the range of education of the pre-schooler outside the classroom, outside the kindergarten to the local community, which due to its specificity and diversity conditions greater flexibility of the learning process.